Komunikasi Antar Generasi Dalam Melestarikan Ritual Hindu Di Candi Prambanan - Wibowo, Gatot; Widayati, MM. Sri; Yoga, I Dewa Gede (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2025)
Prambanan Temple, as one of the Hindu cultural heritage sites in Indonesia, holds significant historical and spiritual value. The preservation of Hindu rituals within this temple complex opens up avenues for development and innovation, particularly in the context of intergenerational communication. The preservation of Hindu rituals within this temple complex presents challenges, particularly in the context of communication between generations. This research aims to analyze the communication patterns between the older and younger generations in maintaining the continuity of Hindu rituals at Prambanan Temple. The research methodology employed is a qualitative approach using in-depth interviews and observations of the community actively engaged in ritual practices. The findings of this study are expected to provide insights into the effectiveness of intergenerational communication as well as to identify factors that either support or hinder the transformation of knowledge and religious practices. These findings may serve as a foundation for more effective cultural preservation strategies, both for local communities and the government.